(untitled) (Bodhi Path, 2020)
The negative predicate anattā, used to convey the idea that certain things are not the self, i.e. are the non-self, is used not as an adjective but as a noun. The proof is in the fact that it stays unchanged whatever be the subject’s gender and number: rūpam anattā, vedanā anattā, saṅkhārā anattā, viňňaṇam anattā.1 The practical consequence of this is important. What is affirmed by means of the predicate anattā is not an abstract idea, but a concrete existing reality. Therefore, if it is said that material form (rūpaṁ) is anattā, and not merely said that material form exhibits the characteristic of non-selfhood, but that material form is part of the totality of things constituting the non-self (anattā) a totality of things opposed and contradictory to the self (attā). This confirms the polarity existing in the nikāyas between the self and non-self, implying the reality of two positive entities, possessed of antithetical natures. In this ideological set up the reality of anattā, of which no one doubts, implies the reality of attā, there being a continual existential confict between the two, until attā succeeds in asserting its absolute independence from the former.